Decorating the pottery of the Ljubljana culture and the Litzen pottery – an experimental archaeology case study - Leghissa, Elena (Arheološki vestnik, 2015)
The article examines the technique used to decorate the Late Copper Age and Early Bronze Age pottery of the Ljubljana culture and the Litzen pottery. In literature, the technique is known under various names and is explained in different ways. A correct explanation being of both chronological and cultural significance, I set out to conduct experiments aimed at determining the tools used to make the characteristic cord impressions. The experiments have shown that the decoration was most probably made with a flat tool, around which a cord or fibres of either animal or plant material were wrapped.